2015
DOI: 10.1111/eos.12241
|View full text |Cite
|
Sign up to set email alerts
|

Enamel organ proteins as targets for antibodies in celiac disease: implications for oral health

Abstract: Enamel defects in permanent and deciduous teeth may be oral manifestations of celiac disease. Sometimes they are the only sign that points to this underdiagnosed autoimmune pathology. However, the etiology of these specific enamel defects remains unknown. Based on previously reported cross-reactivity of antibodies to gliadin with the enamel proteins, amelogenin and ameloblastin, we analyzed (using immunohistochemistry) the ability of anti-gliadin IgG, produced during untreated disease, to recognize enamel orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 39 publications
1
7
0
4
Order By: Relevance
“…However, some of the anti‐Emdogain/amelogenin IgG reactivity appeared not to be a result of anti‐gliadin cross‐reactivity (11), which the epitope mapping in the current study revealed may be to the N‐ and/or C‐terminal regions. Moreover, serum IgG from Emdogain‐high titer CeD children, but not from low‐titer CeD children or controls, showed ability to detect amelogenin in situ in the pre‐enamel, similarly to what SÓÑORA et al, reported for adult women with CeD (17). To what extent anti‐AMELX IgG may interfere with normal amelogenesis would depend on the amelogenin epitope(s) to which these antibodies bind.…”
Section: Discussionsupporting
confidence: 78%
“…However, some of the anti‐Emdogain/amelogenin IgG reactivity appeared not to be a result of anti‐gliadin cross‐reactivity (11), which the epitope mapping in the current study revealed may be to the N‐ and/or C‐terminal regions. Moreover, serum IgG from Emdogain‐high titer CeD children, but not from low‐titer CeD children or controls, showed ability to detect amelogenin in situ in the pre‐enamel, similarly to what SÓÑORA et al, reported for adult women with CeD (17). To what extent anti‐AMELX IgG may interfere with normal amelogenesis would depend on the amelogenin epitope(s) to which these antibodies bind.…”
Section: Discussionsupporting
confidence: 78%
“…However, different immune or genetic genesis of lesions cannot be excluded. T-lymphocytes may have a role in attacking the enamel [ 30 , 31 ], and there may be an association between dental enamel effects and the haplotype HLA-DR3 even in the general population. On the contrary, the DR5-DR7 phenotype has been associated with protection from damage to the enamel, explaining why not all CD patients suffer from enamel hypoplasia [ 19 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sóñora et al [ 43 ], based on previously reported cross-reactivity of antibodies to gliadin with the enamel proteins, amelogenin and ameloblastin, investigated the ability of antigliadin IgG to recognize enamel organ structures. Strong staining of the enamel matrix and of the layer of ameloblasts was observed with serum samples from women with celiac disease.…”
Section: Discussionmentioning
confidence: 99%